THE MODERN INTERIOR - Akramov Kozimjon Ibragimjon o‘g‘li (Journal of new century innovations, 2023)
As an independent direction in the arrangement of premises, interior design has emerged relatively recently, although the desire to add variety to the environment has always been inherent in man. The furnishings have the most direct impact on our psychological and emotional state, and hence the so widespread desire to periodically change the color scheme and appearance of our apartment. Usually, interior design is primarily associated only with the performance of a decorative function, as it has a powerful visual impact. As an independent direction in the arrangement of premises, interior design has emerged relatively recently, although the desire to add variety to the environment has always been inherent in man. The furnishings have the most direct impact on our psychological and emotional state, and hence the so widespread desire to periodically change the color scheme and appearance of our apartment. Usually, interior design is primarily associated only with the performance of a decorative function, as it has a powerful visual impact.